The Society for Obstetric Anesthesia and Perinatology Consensus Statement on the Anesthetic Management of Pregnant and Postpartum Women Receiving Thromboprophylaxis or Higher Dose Anticoagulants. (March 2018) - Leffert, Lisa; Butwick, Alexander; Carvalho, Brendan; Arendt, Katherine; Bates, Shannon M.; Friedman, Alex; Horlocker, Terese; Houle, Timothy; Landau, Ruth; Dubois, Heloise; Fernando, Roshan; Houle, Tim; et al.
Abstract : Venous thromboembolism is recognized as a leading cause of maternal death in the United States. Thromboprophylaxis has been highlighted as a key preventive measure to reduce venous thromboembolism–related maternal deaths. However, the expanded use of thromboprophylaxis in obstetrics will have a major impact on the use and timing of neuraxial analgesia and anesthesia for women undergoing vaginal or cesarean delivery and other obstetric surgeries. Experts from the Society of Obstetric Anesthesia and Perinatology, the American Society of Regional Anesthesia, and hematology have collaborated to develop this comprehensive, pregnancy-specific consensus statement on neuraxial procedures in obstetric patients receiving thromboprophylaxis or higher dose anticoagulants. To date, none of the existing anesthesia societies' recommendations have weighed the potential risks of neuraxial procedures in the presence of thromboprophylaxis, with the competing risks of general anesthesia with a potentially difficult airway, or maternal or fetal harm from avoidance or delayed neuraxial anesthesia. Furthermore, existing guidelines have not integrated the pharmacokinetics and pharmacodynamics of anticoagulants in the obstetric population. The goal of this consensus statement is to provide a practical guide of how to appropriately identify, prepare, and manage pregnant women receiving thromboprophylaxis or higher dose anticoagulants during the ante-, intra-, and postpartum periods. The tactics to facilitate multidisciplinary communication, evidence-based pharmacokinetic and spinal epidural hematoma data, and Decision Aids should help inform risk–benefit discussions with patients and facilitate shared decision making.